2006
DOI: 10.1097/01.brs.0000217692.90624.ab
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Stabilization With Anterior Lumbar Intervertebral Fusion–A Radiologic Review

Abstract: The addition of pedicle screw fixation at ALIF produces a significant increase in the rate of interbody fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 23 publications
0
23
1
2
Order By: Relevance
“…Li et al [9] reported a range between 51.9 and 88.9 % fusion in a literature review. Anjarwalla et al [21] assessed the fusion rate of one stand-alone cage ALIF versus the same ALIF cage with different techniques of posterior supplemental fixation. The fusion rate for the stand-alone cage was 51 % versus 89 % and 88 % for the two groups supplemented with pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [9] reported a range between 51.9 and 88.9 % fusion in a literature review. Anjarwalla et al [21] assessed the fusion rate of one stand-alone cage ALIF versus the same ALIF cage with different techniques of posterior supplemental fixation. The fusion rate for the stand-alone cage was 51 % versus 89 % and 88 % for the two groups supplemented with pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
“…Tzermiadianos et al [75] postulated that from a biomechanical point of view, ALIF and additional ATB plating seemed to be a reasonable alternative to ALIF with posterior pedicle screw instrumentation to enhance ALIF cage stability. Furthermore, previous biomechanical, clinical and radiological studies have reported that ASAF devices such as the one that was investigated in the current study or similarly configured implants provide sufficient biomechanical stability [21,70,[75][76][77][78][79][80][81].…”
Section: Interbody Fusion Assessmentmentioning
confidence: 99%
“…In the orthopaedic implant field, several reports have found fibrous capsules around implants of metallic [18, 19] or polymeric nature [20-22]. This type of failure is commonly attributed to toxic wear debris phagocytosed by macrophages and other cells of the surrounding tissue [23-25].…”
Section: Introductionmentioning
confidence: 99%